2019
DOI: 10.1111/ctr.13730
|View full text |Cite
|
Sign up to set email alerts
|

The curative treatment of familial hypercholesterolemia: Liver transplantation

Abstract: BackgroundFamilial hypercholesterolemia (FH) is an autosomal dominant genetic disorder characterized by premature mortal cardiovascular complications. Liver transplantation (LT) is the only curative treatment option. In this study, the long‐term clinical follow‐up data of 8 patients who underwent LT with a diagnosis of FH in our center are presented.Materials and MethodsA total of 638 LT were performed between December 1985 and June 2019 at Baskent University, of which 8 patients underwent LT with a diagnosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 31 publications
1
5
0
Order By: Relevance
“…Although substantially lowering the LDL-C level may be achieved with LT, the reduction in LDL-C levels may fluctuate and rebound, and the progression of ASCVDs can be problematic. In line with our results, previous studies have reported fluctuating LDL-C levels in HoFH patients after LT [ 30 , 31 , 32 , 33 , 34 , 37 ], perhaps because of residual extrahepatic LDL receptors and immunosuppressive drug-induced hyperlipidemia [ 37 ]. Consequently, postoperative lipid-lowering therapy may be crucial for achieving acceptable LDL-C levels and halting progression of ASCVDs.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…Although substantially lowering the LDL-C level may be achieved with LT, the reduction in LDL-C levels may fluctuate and rebound, and the progression of ASCVDs can be problematic. In line with our results, previous studies have reported fluctuating LDL-C levels in HoFH patients after LT [ 30 , 31 , 32 , 33 , 34 , 37 ], perhaps because of residual extrahepatic LDL receptors and immunosuppressive drug-induced hyperlipidemia [ 37 ]. Consequently, postoperative lipid-lowering therapy may be crucial for achieving acceptable LDL-C levels and halting progression of ASCVDs.…”
Section: Discussionsupporting
confidence: 92%
“…Other attractive approaches, such as gene therapy [ 26 , 27 ] or hepatocyte transplantation [ 28 ], are largely underexplored. Finally, LT has been a last resort for pediatric patients with HoFH since the 1980s [ 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. In our case series, none of these six children with HoFH received aggressive lipid-lowering therapy with mipomersen, evolocumab, evinacumab, or LDL apheresis before LT, which may reflect a real problem with undertreatment in settings where availability of lipid-lowering therapy is limited.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Limited studies are available on long-term survival after treatment of HoFH with LT. Results from an Iranian study [21,22] indicated that survival rates in HoFH patients after LT at 0.5, 1 and 5 years were 92%, 94% and 91%, respectively. In another case on the long-term survival in a HoFH patient who underwent OLT from a cadaveric donor liver at 12 years after a diagnosis of HoFH, the patient's skin xanoma and atherosclerotic plaques were completely resolved at 9 years after the transplantation and endothelial function was normal [14].…”
Section: Discussionmentioning
confidence: 99%
“…In the post-LT period, the cholesterol levels fall to normal within a week’s time. LT by improving the dyslipidemia is known to prevent the progression to coronary artery disease[ 69 , 70 ]. Pathological findings in liver include accumulation of lipid in hepatocytes and Kupffer cells.…”
Section: Group Bmentioning
confidence: 99%